Anomalous electrocaloric behaviors in (anti)ferroelectrics: a mini-review - Li, Feng; Wang, Chunchang; Shan, Lei (Frontiers in Chemistry, 2024)
Solid-state cooling, represented by the electrocaloric effect (ECE) in (anti)ferroelectric materials, has emerged as an alternative green refrigeration technology by virtue of its high efficiency and miniaturization and is expected to substitute conventional vapor-compression. Significant progress has been made in developing high-performance EC materials since its revival. However, anomalous EC behaviors are frequently observed, including asymmetric and negative EC profiles, and the physical mechanism behind this is still under debate. Its rationalization is of great importance since full utilization of anomalous EC behaviors could enhance EC strength and/or cooling capacity. This mini-review gives a brief overview of research advances in EC anomalies in (anti)ferroelectrics with the hope of provoking thought on the design of reconstructed refrigeration cycles and superior EC materials for application in solid-state cooling devices.